Private equity project - analysis of Delo industrial adhesives - Kuntz, Gabriel (2022)
This Field Lab Work Project in form of a Private Equity Challenge aims to take the perspective of private equity funds and their deal process. The objective is to analyze a target company, develop an investment strategy and model a leveraged buyout for the chosen company. In this case, our group identified “DELO –Industrial Adhesives” as an attractive target company. Our following analysis aims at convincing the investment committee to theoretically agree with leveraged buyout of DELO.